Synergistic toxicity of some food additives used in non-alcoholic beverages on renal tubular epithelial cells: Toxicity of food additives on renal tubular epithelial cells - Meng, Xiaopeng; Yang, Yiran; Zhang, Jing; Su, Jianting; Li, Gang; Liu, Shuxia (Cellular and Molecular Biology, 2023)
Evidences supported many food additives (FAs) possess toxicity to human health due to chronic excessive exposure. Global hygienic standards strictly limit the dosage of each FA and mixture of the same functional FAs. However, the synergetic effects caused by the combination of FAs with different functions require careful evaluation. In the present study, the content of each FA in beverages was determined by HPLC-UV-Vis detection. The cytotoxic effects of selected typical FAs alone or their combination were evaluated in human renal tubular epithelial cells. Mathematical Modeling and bioinformatics methods were employed to evaluate the toxicity of FAs and to predict the key target proteins of FAs on renal tubular cell toxicity, which were verified by western blot. The results indicated above 5 FAs were used in each surveyed beverage. The content of each FA and the respective ratios of the same functional FAs in each beverage did not exceed the maximum permitted level. But it was intensively shown that the significant synergistic cytotoxicity for the combination of FAs with lower concentration. The intercellular signaling transduction pathways including JNK/STAT, PI3P/AKT, and MAPK pathways, which could also be activated by PDGF signaling, were predicted to be involved in Fas-induced cytotoxicity. The increased expression of p-STAT3, p-JNK and p-AKT was associated with renal tubular injury. The current study implied the synergistic cytotoxic effect caused by multiple FAs at no toxic dosages via activated cellular transduction pathways regulating cell survival and apoptosis function, which warning of the synergistic toxic effects of different types of FAs.